Food beliefs - Costanigro, Marco, author; Deselnicu, Oana, author; Kroll, Stephan, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2013)
Product attributes (such as whether the product is organic) have been used to analyze consumer choices in market data. However, rather than generating utility directly, these attributes may instead be valued as a signal of a product outcome (such as nutritional benefits). For example, organic products may be valued because they are perceived as healthier, or they may be perceived as having a reduced environmental impact; "no sodium added" may communicate healthiness and improved flavor; and "cage free" may suggest improved animal welfare. In this paper, we examine how attribute information on food packaging influences outcome expectations. We show that when attributes are labeled but outcomes are unknown, the utility derived from the product attributes depends on the tradeoffs between alternative outcomes (preferences) and the perception of how those attributes determine outcomes (beliefs). In the second part of the research, we study consumer beliefs: specifically, how food labels and other package information influence expectations about nutritional and environmental outcomes for fluid milk products. Here we provide evidence that some attribute labels can bias consumers' expectations and are therefore potentially misleading.
November 2013.
Keywords: attributes; nutritional value; food labels; food packaging; consumer beliefs; environmental impacts